Game 3D “Lawan Narkoba” Menggunakan Metode Game Development Life Cycle (GDLC) - Mei Roselina Siregar; Nelmiawati Nelmiawati; Muhammad Ikhlas Habibi (Politeknik Negeri Batam, 2020)
Drugs have an adverse impact towards young generation. The Increasing number of young generation get involved in this situation has been impacted a serious problem every year in Indonesia. National Narcotics Agency report about 3.5 million people has abused drug usage in 2017, in which 1.4 million are regular users and one million has become a drug addict. Thus, education and preventive are keep being done to protect them. Several Android Games possibly help as a preventive way as well as an effective learning media. The research works on a Game as a preventive way to young generation. This two level game tells the user about several ways to prevent from drugs such as the impact of how to save themselves from drugs, as well as type of drugs that are available. By accomplishing this, GDLC (Game Development Life Cycle) method has been used. The result shows that 97,3% of the contents can be understood by 30 people of respondents.